Dynamic supply chain management: Applying the qualitative data analysis software - Saad, Shatina; Mohamed Udin, Zulkifli; Hasnan, Norlena (2014)
Analysis of data has been known as one of the most significant stages in a qualitative research process.The purpose of this article is to share elements for understanding during the process of preparing an analysis using the qualitative data analysis (QDA) software. ATLAS.ti version 7.1.7, the QDA software, provides some very valuable tools in academic research, especially for social science fields.This paper offers a review of dynamic capabilities in dynamic supply chain management by utilizing QDA software package. Moreover, steps how to use ATLAS.ti and figures are provided to describe the research presented with examples.This will serve as a guideline for beginner's researchers in qualitative research who are applying the QDA software, particularly ATLAS.ti. As such, use of the analysis outlined in this article should help to support the rigor in qualitative research.